ASSESSMENT OF GLYCEMIC CONTROL IN CHILDREN WITH TYPE 1 DIABETES MELLITUS BASED ON HbA1c AND TIR INDICATORS - Yunusova, Shahzoda; Sharikhsieva, Mukhlisa; Khodjaeva, Nodira (Uzbekistan Open Conference, 2026)
Type 1 diabetes mellitus has a significant impact on child development, especially in the presence of prolonged hyperglycemia. Achieving and maintaining adequate glycemic control in children with type 1 diabetes mellitus remains one of the key clinical challenges, particularly at school age. This study aimed to assess glycemic control in children with type 1 diabetes mellitus in real clinical practice based on HbA1c and time in range indicators obtained using continuous glucose monitoring. A cross-sectional observational study included 45 children with type 1 diabetes mellitus receiving basal-bolus insulin therapy. Medical records were analyzed to assess age, sex, disease duration, insulin therapy regimen, HbA1c level, and TIR indicators obtained using continuous glucose monitoring. TIR was calculated as the proportion of time during which glucose levels remained within the range of 70–180 mg/dL over the last 14 days, provided that sensor data coverage was at least 70%. The mean age of the examined children was 10.98 ± 3.66 years, and the mean disease duration was 2.91 ± 2.22 years. Despite intensive insulin therapy, glycemic control indicators remained markedly unsatisfactory. The mean HbA1c level was 11.64 ± 2.01%, while the mean TIR was only 13.18 ± 3.70%, which is significantly below the recommended target values for the pediatric population. Most patients received basal-bolus therapy using insulin glargine as the basal component. The findings indicate pronounced glycemic variability and insufficient metabolic control in real clinical practice. The use of continuous glucose monitoring and analysis of TIR provide additional information on short-term glycemic fluctuations and complement HbA1c assessment. The predominance of school-age children in the study group emphasizes the need to strengthen diabetes care during school time, improve self-monitoring, and optimize therapy based on continuous glucose monitoring data.
Keywords: type 1 diabetes mellitus; children; glycemic control; HbA1c; time in range; TIR; continuous glucose monitoring; CGM; insulin therapy; school age